A patient presenting with recurrent post-prandial abdominal discomfort and vomiting - Saha, Ashis Kumar; Dhar, Payodhi; Dhar, Payodhi; Roy, Abhiparna; Roy, Abhiparna; Roy, Soumesh; Roy, Soumesh (International Journal of Research in Medical Sciences, 2017)
Duodenal diverticulum is the second most common diverticulum of gastrointestinal tract. Among duodenal diverticulum, incidence of intramural duodenal diverticulum is 100 as per report till date. It is usually asymptomatic, but in middle or adult age, it may present with postprandial abdominal discomfort, often complicates in the form of bleeding, perforation or rarely neoplasm. So, this congenital duodenal deformity requires urgent definitive treatment. Here we presented a case presenting with postprandial abdominal discomfort with occasional vomiting. He was advised upper gastrointestinal endoscopy. It showed evidence of duodenal septa at the junction of 1st and 2nd part. Scope was negotiated through one channel. He was advised barium meal of stomach, duodenum and follow through, which ultimate demonstrated presence of a rare abnormality, duodenal intramural diverticulum, which if not treated, can produce severe complication in future.